Chapter Introduction Socialising tourism: reimagining tourism's purpose - Higgins-Desbiolles, Freya (Taylor & Francis, 2021)
"An agenda for socialising tourism seeks to address the disbenefits associated with neoliberal corporatised forms of tourism by re-orienting tourism in important ways. Socialising tourism can be viewed as a revival and extension of earlier thinking by Higgins-Desbiolles on "tourism as a social force". In later work, Higgins-Desbiolles proposed socialising tourism meant "[...]to make tourism responsive and answerable to the society in which it occurs", suggesting that it is both the tourist and the tourism industry that must be socialised into respecting the local community and serving their needs and interests. This chapter considers: what might socialising tourism mean; why does tourism need to be socialised; how might tourism be socialised; and finally, what might we ask of tourism. In particular, socialising tourism necessitates a change in our values, based on an understanding of our interdependency, an interest in the "Other", appreciation of human-environmental relations and commitment to practices of respect, relationships, reciprocity and responsibility. Such work sets a promising agenda to rethink and reset tourism for social and ecological justice."